The Penguin book of witches - Howe, Katherine (Penguin classics, 2014)
"Chilling real-life accounts of witches, from medieval Europe through colonial America: from a manual for witch hunters written by King James himself in 1597, to court documents from the Salem witch trials of 1692, to newspaper coverage of a woman stoned to death on the streets of Philadelphia while the Continental Congress met, The Penguin Book of Witches is a treasury of historical accounts of accused witches that sheds light on the reality behind the legends. Bringing to life stories like that of Eunice Cole, tried for attacking a teenage girl with a rock and buried with a stake through her heart; Jane Jacobs, a Bostonian so often accused of witchcraft that she took her tormentors to court on charges of slander; and Increase Mather, an exorcism-performing minister famed for his knowledge of witches, this volume provides a unique tour through the darkest history of English and North American witchcraft."--Publisher